2021
DOI: 10.3390/ijms22041798
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Organelles as Molecular Platforms for Axon Growth and Regeneration after Injury

Abstract: Investigating the molecular mechanisms governing developmental axon growth has been a useful approach for identifying new strategies for boosting axon regeneration after injury, with the goal of treating debilitating conditions such as spinal cord injury and vision loss. The picture emerging is that various axonal organelles are important centers for organizing the molecular mechanisms and machinery required for growth cone development and axon extension, and these have recently been targeted to stimulate robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 320 publications
0
15
0
Order By: Relevance
“…In addition, spatial and temporal alteration of circulating fatty acids may compromise CNS function and repair under pathological conditions including CNS trauma and neurodegenerative diseases. Correct positioning of organelles for membrane trafficking, lipid exchange and energy production requires a complex interplay between various organelles and molecular motors [ 249 ]. The fabrication of new inducible and reversible systems may allow us to gain spatiotemporal control over this process [ 250 ], enabling CNS repair with precision.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spatial and temporal alteration of circulating fatty acids may compromise CNS function and repair under pathological conditions including CNS trauma and neurodegenerative diseases. Correct positioning of organelles for membrane trafficking, lipid exchange and energy production requires a complex interplay between various organelles and molecular motors [ 249 ]. The fabrication of new inducible and reversible systems may allow us to gain spatiotemporal control over this process [ 250 ], enabling CNS repair with precision.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated significant developments in tissue-engineered conduits integration to bridge defects of spinal cord injury using various strategies such as cell transplants, degradation products of glial scar or biological cues, and physical guides. The tissue of the spinal cord is not structurally homogeneous but consists of various types of neural cells organized in spatially complex orders. , The locally definite neuronal subtypes firmly affect axonal growth . Consequently, successfully recreating/fabricating patient-specific structures in appropriate clinical shape, size, and structural integrity has progressed by integrating progenitor and neural stem cells with biocompatible 3D-printed scaffolds to evaluate novel therapeutic cues for injuries in the spinal cord. ,,,, Three-dimensional printing approaches are applied in two distinct fields of spinal cord scaffold development: (i) seeding of cells on 3D-printed scaffolds and (ii) 3D printing of bioinks for construct fabrication.…”
Section: Three-dimensional Printing Techniques For Biomimetic Structuresmentioning
confidence: 99%
“…Instead, the membrane sources allowing axonal growth are less characterized. However, complementary observations suggest a role for late and recycling endosomes via mechanisms involving several Rab proteins, including the LRRK2 substrates Rab8 and Rab5 (albeit evidence is weaker for the latter; reviewed in [ 54 ]).…”
Section: Lrrk2 and The Golgi Networkmentioning
confidence: 99%